Plasma-Enhanced Atomic Layer Deposition Assisted Low-Temperature Synthetic Routes to Rationally Designed Metastable c-Axis Aligned Hexagonal In-Zn-O - Hong, Tae Hyun; Kim, Hyeon Woo; Kim, Yoon Seo; Jeong, Hyun Jun; Cho, Sung Beom; Park, Jin Seong (Chemistry of Materials, 2023)
Efforts to design and realize exotic metastable phases with advanced characteristics have been ongoing. However, the challenge lies in identifying their atomic structures and synthetic routes, as most explorations of metastability have relied on intuitions and trial-and-error approaches. Here, we present a computational workflow based on density functional theory (DFT) to rationalize the design of metastable materials. We demonstrate that plasma-enhanced atomic layer deposition (PEALD) is a profitable method for synthesizing target material. By screening the various hypothetical crystal structures of IZO compounds, we have identified the c-axis aligned hexagonal (CAH) In2Zn4O7 as a promising candidate due to its metastability and superior electrical properties compared to a binary metal oxide system. Remarkably, this metastable phase can be synthesized at a significant temperature of 200 °C, compared to the typical crystallization temperature of the IZO system. This low-temperature crystallization is attributed to the distinctive features of PEALD, including tunable atomic order, precise composition control, and adjustable plasma source. By implementing CAH-IZO in thin-film transistor (TFT) applications, we observed desirable characteristics, such as a μFE of 43.4 cm2/V s, despite the low indium (In) content. We believe that this combined approach of PEALD and computational processing can expedite the realization of novel metastable materials, with the potential to expand their applications beyond traditionally explored materials.
Keywords: Computational workflows; Lows-temperatures; Metastabilities; Metastable materials; Metastable phase; Metastables; Plasma-enhanced atomic layer deposition; Structure routes; Synthetic routes; Trial-and-error approach